Ação da L-glutamina via oral por 7 dias na função e estrutura muscular de pacientes com HIV/AIDS em uso de terapia antirretroviral - Mauricio, Daniela de Brito (2016)
The current reality of the clinical condition of patients with HIV / AIDS is not only based on the body's response to infection, but also to adverse reactions caused by antiretroviral therapy. Important changes occur in the body composition of patients with HIV, such as loss of muscle mass. Supplementation with L-glutamine shows that there is improvement in muscle strength of upper limbs in seropositive patients. Objective: To evaluate the action of L-glutamine in the muscles of the lower limbs and upper limbs, after 7 days of supplementation by mouth in patients with HIV/AIDS. Methods: We conducted a clinical study, prospective, randomized HIV- positive volunteers of both sexes who were supplemented for 7 days with L- glutamine group control and maltodextrin in placebo group, both 0,5g / kg / day. Data collection was performed using bioelectrical impedance analysis for body composition and grip strength to check strength of the quadriceps and biceps, made in pre and post supplementation. Results: The groups were differentiated results, both in body composition and muscle strength. In the group supplemented with L- glutamine, there was a reduction in body weight, there was no change in other variables, but had increased biceps strength (p=0,006). In the group supplemented with maltodextrin increased by body weight (p=0,043), followed by muscle mass and loss amount of fat without causing significant changes in body mass index. Conclusion: The L-glutamine, supplemented for 7 days, increases the strength of the biceps muscle of seropositive patients.